Enterprise Mac Security Mac OS X Snow Leopard - Edge, Charles; Barker, William; Hunter, Beau.; Sullivan, Gene.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
A common misconception in the Mac community is that Mac$1 (Bs operating system is more secure than others. While this might be true in certain cases, security on the Mac is still a crucial issue. When sharing is enabled or remote control applications are installed, Mac OS X faces a variety of security threats. Enterprise Mac Security: Mac OS X Snow Leopard is a definitive, expert-driven update of the popular, slash-dotted first edition and was written in part as a companion to the SANS Institute course for Mac OS X. It contains detailed Mac OS X security information, and walkthroughs on securing systems, including the new Snow Leopard operating system. Using the SANS Institute course as a sister, this book caters to both the beginning home user and the seasoned security professional not accustomed to the Mac, establishing best practices for Mac OS X for a wide audience. The authors of this book are seasoned Mac and security professionals, having built many of the largest network infrastructures for Apple and spoken at both DEFCON and Black Hat on OS X security.s
The Big Picture -- Security Quick-Start -- Services, Daemons, and Processes -- Securing User Accounts -- File System Permissions -- Reviewing Logs and Monitoring -- Securing the Ecosystem -- Application Signing and Sandbox -- Securing Web Browsers and E-mail -- Malware Security: Combating Viruses, Worms, and Root Kits -- Encrypting Files and Volumes -- Network Traffic -- Securing Network Traffic -- Setting Up the Mac OS X Firewall -- Securing a Wireless Network -- Sharing -- File Services -- Web Site Security -- Remote Connectivity -- Server Security -- Securing the Workplace -- Network Scanning, Intrusion Detection, and Intrusion Prevention Tools -- Backup and Fault Tolerance -- Forensics.
Keywords: Computer science; Computer Science; Computer Science, general; Electronic books